EVALUASI PEMBELAJARAN PADA KURIKULUM 2013 DENGAN KURIKULUM MERDEKA - Ucok Setia Siregar (Jurnal Al Burhan, 2023)
The implementation of the 2013 Curriculum with the Independent Curriculum has a difference in the presence of obstacles, so that the obstacles encountered affect the learning process. Based on the literature review that has been conducted, the policy of the Minister of Education and Culture, Nadiem Makarim, is known as the Freedom to Learn policy. This policy includes 4 things: The National Standardized School Examination (USBN) is developed by each school; National Examination (UN) changed to Minimum Competency Assessment (AKM) and Character Survey; the freedom of educators to design Learning Implementation Plans (RPP); and flexibility in New Student Admissions (PPDB). The Freedom to Learn Policy has characteristics that emphasize creativity, learning orientation on problem solving, learning based on the demands of society and the world of work, as well as a comprehensive assessment system. This has an impact on the need for the development of learning evaluation.